2021
DOI: 10.1021/acsomega.1c03020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effect of Solid Products and DC Breakdown Characteristics of the HFO1234Ze(E)–N2–O2 Ternary Gas Mixture

Abstract: HFO1234ze(E) is an environmentally friendly SF 6 substitute gas with prominent application potential. To suppress the generation of the HFO1234ze(E) solid decomposition products, which may cause great hazards to the gas–solid insulation strength, a gas mixing scheme screening method based on the reactive force field (ReaxFF) molecular dynamics (MD) simulation was innovatively proposed. The simulation results show that the inhibitory effect of O 2 on the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Normally, the generation of solid by-products will cause dielectric strength deterioration, operational reliability and service life decreases of GIE, which is common in fluorocarbon eco-friendly gases [34][35][36]. As reported by Liu et al, there exists a relatively large voltage drop between the first and second DC breakdown voltage of HFO-1234ze(E)/N 2 gas mixture owing to the generation of solid by-products that increased the surface roughness of electrode under quasiuniform electric field [26]. Soulie et al also found that under the slightly non-uniform electric field, the presence of solid precipitates greatly reduced the DC breakdown voltage of HFO-1234ze(E) [30].…”
Section: Influence Of Solid Precipitation On Breakdown Voltage Of Hfo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, the generation of solid by-products will cause dielectric strength deterioration, operational reliability and service life decreases of GIE, which is common in fluorocarbon eco-friendly gases [34][35][36]. As reported by Liu et al, there exists a relatively large voltage drop between the first and second DC breakdown voltage of HFO-1234ze(E)/N 2 gas mixture owing to the generation of solid by-products that increased the surface roughness of electrode under quasiuniform electric field [26]. Soulie et al also found that under the slightly non-uniform electric field, the presence of solid precipitates greatly reduced the DC breakdown voltage of HFO-1234ze(E) [30].…”
Section: Influence Of Solid Precipitation On Breakdown Voltage Of Hfo...mentioning
confidence: 99%
“…Some of these particles will re-combine to HFO-1234ze(E), and the others will undergo compound reaction to form stable gaseous decomposition by-products such as CF 4 , CHF 3 , C 2 F 6 , C 3 HF 7 (as shown in figure 11(a)). For the gas decomposition mechanism of HFO-1234ze(E) gas mixture, density functional theory or ReaxFF-MD calculations have been conducted by Wang et al [25], Lin et al [24], Liu et al [26]. Relevant results show that HFO-1234ze(E) initially undergoes bond-cleavage reactions to generate CF 3 , F and H radicals, leading to abstraction reaction to form CF 4 , CHF 3 , and C 2 F 6 which is consistent with our experimental results.…”
Section: Generation Mechanism Of Gas By-products and Solid Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…ReaxFF can simulate chemical reactions at the mesoscopic scale, as well as related thermodynamic and kinetic properties, etc., and has been widely used in pyrolysis [19], combustion [20], new materials development [21] and other fields. Recently, it has also been used to study the chemical properties of insulating gases with satisfactory results [22,23]. Liu et al used the ReaxFF method to investigate the impact of an O 2 environment on the decomposition of SF 6 .…”
Section: Introductionmentioning
confidence: 99%